STUDI KOMPARATIF TERHADAP PRINSIP-PRINSIP ASURANSI SYARIAH MENURUT HUKUM ISLAM DAN UNDANG-UNDANG NO. 40 TAHUN 2014 TENTANG PERASURANSIAN - Aldi Rinaldi; Muhammad Fauzan Januri; Jaenudin Jaenudin (IAIN Syekh Nurjati Cirebon, 2022)
This research is entitled a comparative study of the principles of sharia insurance according to Islamic law and Law No. 40 of 2014 concerning insurance. In its operations, in addition to complying with the legal terms of the agreement, insurance must also comply with the principles of insurance law. The purpose of these principles is to provide a framework within which all parties to a transaction will receive fair and proper treatment. This study aims to discuss the principles of insurance law in Islam and the principles of insurance in Law No. 40 of 2014 concerning insurance by conducting a comparative study which is expected to find similarities and differences. The research method used by the author is using descriptive analysis and comparative research, the data collection technique used is library research. The results of this study there are six principles of sharia insurance in Islamic law, namely; the Principle of Insurable Interest, the Principle of Utmost Good Faith, the Principle of Indemnity, the Principle of Subrogation, the Principle of Proximate Cause, and the Principle of Contribution. While the principles of sharia insurance contained in Law No. 40 of 2014 is the application of sharia principles in accordance with the DSN MUI fatwa, then regarding legal relations in insurance agreements that take provisions from KHES, and legal consequences in insurance which in case of disputes are resolved through mediation.